2012
DOI: 10.1021/es301297z
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Phenomena at the CO2–Brine–Mineral Interface: Implications for Geologic Carbon Sequestration

Abstract: Geologic carbon sequestration (GCS) in deep saline aquifers results in chemical and transport processes that are impacted by the wettability characteristics of formation solid phases in contact with connate brines and injected CO(2). Here, the contact angle (θ) at the CO(2)-brine-mineral interface is studied for several representative solids including quartz, microcline, calcite, kaolinite, phlogopite, and illite under a range of GCS conditions. All were found to be water wetting (θ < 30°) with subtle but impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
163
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 32 publications
9
163
3
Order By: Relevance
“…Average contact angles on flat surface inside micromodel at pressure of one and eight megapascals are 62° ± 7° and 49° ± 21°, respectively, in agreement with Kim et al [58] observations showing a wide range of contact angles from 40° to 80° inside a uniform micromodel. Contact angles on a flat surface in this study are higher than those shown in previous sessile drop or captive bubble tests with large droplet of water or bubble of CO2 (i.e., 8° to 45° on silica or glass surface) [18,22,43,[50][51][52]. This could be due to the micro-scaled CO2 bubble size on a flat surface inside the micromodel of [18,22,43,[50][51][52].…”
Section: Comparing Contact Angle Of Bubbles On Flat Surface With Contcontrasting
confidence: 76%
See 2 more Smart Citations
“…Average contact angles on flat surface inside micromodel at pressure of one and eight megapascals are 62° ± 7° and 49° ± 21°, respectively, in agreement with Kim et al [58] observations showing a wide range of contact angles from 40° to 80° inside a uniform micromodel. Contact angles on a flat surface in this study are higher than those shown in previous sessile drop or captive bubble tests with large droplet of water or bubble of CO2 (i.e., 8° to 45° on silica or glass surface) [18,22,43,[50][51][52]. This could be due to the micro-scaled CO2 bubble size on a flat surface inside the micromodel of [18,22,43,[50][51][52].…”
Section: Comparing Contact Angle Of Bubbles On Flat Surface With Contcontrasting
confidence: 76%
“…Contact angles on a flat surface in this study are higher than those shown in previous sessile drop or captive bubble tests with large droplet of water or bubble of CO2 (i.e., 8° to 45° on silica or glass surface) [18,22,43,[50][51][52]. This could be due to the micro-scaled CO2 bubble size on a flat surface inside the micromodel of [18,22,43,[50][51][52]. This could be due to the micro-scaled CO 2 bubble size on a flat surface inside the micromodel of the present study in comparison with the other studies with larger dimension of bubble ranging from a few to tens of millimeter.…”
Section: Comparing Contact Angle Of Bubbles On Flat Surface With Contcontrasting
confidence: 72%
See 1 more Smart Citation
“…Previous work in the CO 2 storage literature related to the changing magnitude of the chemical potential of water and/or adsorptive and capillary water focuses mainly on: 1) near-wellbore saline water evaporation and concomitant salt precipitation that may reduce scCO 2 injection rates due to permeability losses [16,17,[28][29][30]; 2) chemical reactivity under humid scCO 2 including precipation-dissolution and water intercalation in clays as a function of water content in scCO 2 [7,10,[31][32][33][34][35][36]; and 3) laboratory observation or theoretical estimation of thickness of water films in scCO 2 [26,27,37]. Common approaches for assessing near-wellbore dry-out, in calculating water activity in the CO 2 -rich phase, typically neglect any effects of capillary potential or surface adsorption potential on the total chemical potential of water [e.g., see 36,38].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alteration that changes surface mineralogy or morphology can lead to altered wettability. Mineral wetting properties strongly affect reservoir permeability with respect to water and the supercritical phase, play a key role in determining integrity of caprock seals, and control capillary and residual trapping processes and hence, reservoir storage capacity estimates [79].…”
Section: Introductionmentioning
confidence: 99%